Adaptation of exercise‐induced stress in well‐trained healthy young men. Issue 1 (11th December 2016) - JanssenDuijghuijsen, Lonneke M.; Keijer, Jaap; Mensink, Marco; Lenaerts, Kaatje; Ridder, Lars; Nierkens, Stefan; Kartaram, Shirley W.; Verschuren, Martie C. M.; Pieters, Raymond H. H.; Bas, Richard; Witkamp, Renger F.; Wichers, Harry J.; et al.
Abstract : New Findings: What is the central question of this study? Exercise is known to induce stress‐related physiological responses, such as changes in intestinal barrier function. Our aim was to determine the test–retest repeatability of these responses in well‐trained individuals. What is the main finding and its importance? Responses to strenuous exercise, as indicated by stress‐related markers such as intestinal integrity markers and myokines, showed high test–retest variation. Even in well‐trained young men an adapted response is seen after a single repetition after 1 week. This finding has implications for the design of studies aimed at evaluating physiological responses to exercise. Strenuous exercise induces different stress‐related physiological changes, potentially including changes in intestinal barrier function. In the Protégé Study (ISRCTN14236739;www.isrctn.com ), we determined the test–retest repeatability in responses to exercise in well‐trained individuals. Eleven well‐trained men (27 ± 4 years old) completed an exercise protocol that consisted of intensive cycling intervals, followed by an overnight fast and an additional 90 min cycling phase at 50% of maximal workload the next morning. The day before (rest), and immediately after the exercise protocol (exercise) a lactulose and rhamnose solution was ingested. Markers of energy metabolism, lactulose‐to‐rhamnose ratio, several cytokines and potential stress‐related markers were measured at rest and during exercise. In addition, untargeted urine metabolite profiles were obtained. The complete procedure (Test) was repeated 1 week later (Retest) to assess repeatability. Metabolic effect parameters with regard to energy metabolism and urine metabolomics were similar for both the Test and Retest period, underlining comparable exercise load. Following exercise, intestinal permeability (1 h plasma lactulose‐to‐rhamnose ratio) and the serum interleukin‐6, interleukin‐10, fibroblast growth factor‐21 and muscle creatine kinase concentrations were significantly increased compared with rest only during the first test and not when the test was repeated. Responses to strenuous exercise in well‐trained young men, as indicated by intestinal markers and myokines, show adaptation in Test–Retest outcome. This might be attributable to a carry‐over effect of the defense mechanisms triggered during the Test. This finding has implications for the design of studies aimed at evaluating physiological responses to exercise. Abstract :